2014
DOI: 10.5598/imafungus.2014.05.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on generic names competing for use in Leotiomycetes (Ascomycota)

Abstract: In advancing to one scientific name for fungi, this paper treats genera competing for use in the phylogenetically defined class Leotiomycetes except for genera of Erysiphales. Two groups traditionally included in the so-called “inoperculate discomycetes” have been excluded from this class and are also not included here, specifically Geoglossomycetes and Orbiliomycetes. A recommendation is made about the generic name to use in cases in which two or more generic names are synonyms or taxonomically congruent alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 116 publications
(144 reference statements)
2
101
0
1
Order By: Relevance
“…The former (anamorph: unknown) occurs on branches and bare wood of trees and shrubs (Sutton 1980;de Gruyter et al 2010). The latter is an anamorph of the discomycetous genus Tympanis (Johnston et al 2014).…”
Section: Occurrence Of Other Frequent Fungal Speciesmentioning
confidence: 99%
“…The former (anamorph: unknown) occurs on branches and bare wood of trees and shrubs (Sutton 1980;de Gruyter et al 2010). The latter is an anamorph of the discomycetous genus Tympanis (Johnston et al 2014).…”
Section: Occurrence Of Other Frequent Fungal Speciesmentioning
confidence: 99%
“…For example, sequences attributed to M. cinerea currently in GenBank probably represent several distinct and distantly related species based on their dissimilar ITS sequences. Genetic and morphological links with several other teleomorph genera also have been indicated, including Phaeomollisia (Johnston et al 2014) and Vibrissea (Hamad and Webster 1988, Wang et al 2006b, Grünig et al 2009). Consequently mollisoid apothecia may be candidate sexual states for some endophytes known only by their asexual morphs or sterile cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobs et al 2001, Day et al 2012. Phaeomollisia piceae recently was combined into Phialocephala based on phylogenetic placement within a major clade of Phialocephala (Johnston et al 2014), resulting in 29 currently accepted species in this genus (Index Fungorum 2015, Wong et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Kendr. known only by asexual states, are also included in the family (Kirk et al 2008;Johnston et al 2014). Acephala was erected for the non-sporulating species of Phialocephala that contain a small group of dark septate root endophytes (Grünig and Sieber 2005;Grünig et al 2008;Grünig et al 2009;Münzenberger et al 2009;Wang et al 2009;Day et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Acephala was erected for the non-sporulating species of Phialocephala that contain a small group of dark septate root endophytes (Grünig and Sieber 2005;Grünig et al 2008;Grünig et al 2009;Münzenberger et al 2009;Wang et al 2009;Day et al 2012). About 80 species are currently accepted in the family, among which two species are in Acephala, six in Chlorovibrissea, one in Leucovibrissea, 33 in Phialocephala, and 36 in Vibrissea (Grünig et al 2008;Kirk et al 2008;Grünig et al 2009;Münzenberger et al 2009;Wang et al 2009;Day et al 2012;Johnston et al 2014;Sandoval-Leiva et al 2014;Index Fungorum 2017). The previous phylogenetic studies on the vibrisseaceous fungi showed that Chlorovibrissea and Vibrissea are not closely related, and the family was presumably polyphyletic (Wang et al 2006;Sandoval-Leiva et al 2014).…”
Section: Introductionmentioning
confidence: 99%